Penerapan Teknik Parallel Imaging Pada Pesawat MRI 0,35 Tesla Untuk Optimalisasi Kualitas Informasi Anatomi Pada MRI Lumbal Pembobotan T1WI dan T2WI Potongan Sagital - Gatot Murti Wibowo; Dartini Dartini; Hari Prayitno (Jurnal Imejing Diagnostik (JImeD), 2015)
Background : Parallel imaging is one of the MRI Scanning techniques used to reduce the overall scan time when the patients with unvoluntary movement being examined with a low magnetic field of 0,35 T.  This research aims to determine the difference between the clinical image quality of the conventional turbo spin echo (TSE) with mSENSE and that of the TSE with GRAPPA parallel imaging techniques from which resulting the MRI T1 and T2 Weighted Images (T1WI and T2WI) sagittal view of lumbar spines, and to define the techniques that clinically provide the most approriate anatomical information.Methods :  This experimental study is made performed by the MRI 0.35 T in which 10 patients who had hernia nucleus pulposus (HNP) desease participated in the experiments ramdomly. The appointed Radiologists blended in the image evaluation using an image checklist to assess the visualisation of anatomical organs on the resulted sagittal lumbar MRI T1WI and T2WI. The two non-parametric statistical tools, Friedman test and the post hoc Wilcoxon matched pairs test, is used to analyze all the data descriptively. Testing the resesearch hypotheses with 95% of confident interval is to proved the differences between resulted sagittal lumbar MRI T1WI and T2WI..Results : The results shown there is a significant difference on the image quality of anatomical information when conventional TSE, parallel imaging-mSENSE and -GRAPPA, with T1WI are applied in the imaging techniques. When those imaging techniques are employed to obtain T2WI, the result is not significant in  contrast.Conclusion : Good imaging techniques with adequate clinical image quality are ranked sequently as the conventional TSE, the  mSENSE and GRAPPA.